Prevention of respiratory disease in weaning calves - Schalles, R.R.; Milleret, R.J.; McKee, M.; Olson, J.R.; Evans, Jack; Carnahan, D.L. (Kansas State University. Agricultural Experiment Station, 2011)
Respiratory diseases of weanling calves are a continuous problem for ranchers. Each case is estimated to represent a $10 to $20 loss through veterinary costs, decreased gains, and death losses. There is also some question as to the effectiveness of certain preventative treatments. Few reliable experiments have compared medicative and management procedures of disease preventions. We evaluated preweaning vaccinations and weaning management practices.
Keywords: Beef; Respiratory diseases; Weaning